Regional Economic Outlook, October 2008, Euope : Dealing with Shocks. (Regional Economic Outlook, 2008)
The confluence of multiple adverse shocks-the turbulence in financial markets, high commodity prices, and the appreciation of the exchange rate-have depressed growth in Europe. At the same time commodity prices increases have boosted headline inflation. While containing inflation remains a major concern, supporting the recovery is likely to gain policy prominence in the advanced economies. Looking forward, improvements in prudential regulation could mitigate the procyclicality of credit standards, which should help reduce macroeconomic volatility. Cross-border labor flows are generally seen to have beneficial macroeconomic effects.